Population connectivity and dynamics in early-life stages of Atlantic fish communities - Pereira Gabellini, Aurelia; Mariani, Patrizio; Christensen, Asbjørn (Frontiers in Marine Science, 2023)
Introduction Many hypotheses have been suggested to explain recruitment variability in fish populations. These can generally be divided into three groups, either related to: larval food limitation, predation, or transport. Transport mechanisms are central for reproduction in pelagic species and three physical processes, concentration, enrichment, and retention are commonly referred as the fundamental “ocean triads” sustaining larval survival and thus success of reproductive effort. The aim of this study is to investigate linkages between primary production and transport processes of eggs and larvae for the most important commercial fish species in the Atlantic Ocean. Methods We simulated eggs and larvae dispersion using an individualbased model and integrating information on the fish ecology of the major fish stocks. Our work included a review on spawning ground locations, spawning time, eggs and larvae duration. Simulations were performed over a 10-year time period for 113 stocks (17 species) in order to assess variability in dispersion and common trends and factors affecting transport. Results The level of primary production from initial to final position, i.e. from spawning to larval settlement, increased for some stocks (n=31), for others it declined (n=64), and for a smaller group (n=18) there was no substantial changes in level of primary production. Discussion This result implies that larval transport will not necessarily introduce larvae into areas of enhanced food availability expressed by the primary production at the site. These findings thus suggest marked differences in how physical and biological processes interact in the early life of major fish groups in the Atlantic Ocean. The results provide a further insight into fish larval drift and the potential role of primary production in emergence of spawning strategies.